Clinical and imaging features of nonmotor onset seizure in poststroke epilepsy. Issue 8 (10th June 2022) - Fukuma, Kazuki; Ikeda, Shuhei; Tanaka, Tomotaka; Kamogawa, Naruhiko; Ishiyama, Hiroyuki; Abe, Soichiro; Tojima, Maya; Kobayashi, Katsuya; Shimotake, Akihiro; Nakaoku, Yuriko; Nishimura, Kunihiro; Koga, Masatoshi; et al.
Abstract: Objective: Motivated by the challenges raised by diagnosing poststroke epilepsy (PSE), especially in nonmotor onset seizure (non‐MOS), we aimed to investigate the features of non‐MOS, including seizure sequences, patient characteristics, and electrophysiological and imaging findings in PSE. Methods: This observational cohort study enrolled patients with PSE whose seizure onset was witnessed. According to the International League Against Epilepsy (ILAE) 2017 seizure classification, we classified seizure‐onset symptoms into the non‐MOS and MOS groups. We compared the different clinical characteristics between the two groups. Results: Between 2011 and 2018, we enrolled 225 patients with PSE (median age, 75 years), consisting of 97 (43%) with non‐MOS and 128 (57%) with MOS. Overall, 65 (67%) of the patients without MOS had no subsequent convulsions. Multivariable logistic regression analysis showed significant associations of non‐MOS with absence of poststroke hemiparesis (adjusted odds ratio [OR], 1.88; 95% confidence interval [CI], 1.03–3.42), frontal stroke lobe lesions (OR, 2.11; 95% CI, 1.14–3.91), and putaminal stroke lesions (OR, 2.51; 95% CI, 1.22–5.18) as negative indicators. Postictal single‐photon emission computed tomography (SPECT) detected prolonged hyperperfusion in the temporal lobe more frequently in the non‐MOS than in the MOS group (48% vs 31%; p  = .02). The detection rate was higher than spikes/sharp waves in scalp electroencephalography, both in the non‐MOS group (72% vs 33%; p  < .001) and the MOS group (68% vs 29%; p  < .001). Significance: This study provides the clinical features of non‐MOS in patients with PSE. Compared with the patients with MOS, patients with non‐MOS showed less likely subsequent convulsive seizures, highlighting the clinical challenges. Postictal perfusion imaging and negative indicators of the non‐MOS type may help diagnose and stratify PSE.